Effect of UV-radiation on structure and properties of PP nanocomposites - Senatova, S.I.; Senatov, F.S.; Kuznetsov, D.V.; Stepashkin, A.A.; Issi, J.P. (Journal of alloys and compounds, 2017)
Products made of polypropylene (PP) are subject to photodegradation under UV-radiation leading to a change in the physical characteristics of the polymer. The addition of UV-filters, like ZnO nanoparticles, contribute to absorb UV-radiation and protect the polymer matrix. In this study ZnO nanopowder with a particle size of 50 nm was modified by 3-aminopropyltriethoxysilane (APTES) and introduced into the PP matrix. The optimal concentration of nanoparticles was determined. PP-films with a thickness of 100 and 200 μm were obtained. Structural and mechanical characteristics before and after irradiation by UV-radiation were studied by means of FTIR-spectroscopy, XRD, DSC, UV-VIS spectrophotometry and tensile tests. It was observed that UV irradiation of PP leads to the break of molecular chains, therefore releasing more molecular segments released. These segments can move and form a new crystal structure in the initial amorphous phase. The oxidation index of PP increased due to the formation of ketones. ZnO nanoparticles modified by APTES acted as nucleation sites and γ-phase was formed in the polymer. Also, the addition of ZnO-APTES nanoparticles in the polymer promoted absorption of UV-radiation in the wavelength range of 200–400 nm, thus protecting the polymer from degradation. •DSC data demonstrated the presence of two melting peaks of α-PP: α1-α2.•Introduction of 1% wt. ZnO-APTES led to decrease in transmittance and total absorbing in the UV region of 200–380 nm.•ZnO nanoparticles acted as nucleation centers during crystallization of PP from the melt.•ZnO-APTES nanoparticles led to reduction in oxidative degradation of the polymer under the action of UV-radiation.